What Pakistani doctoral students want? A qualitative exploration of their research experiences. Issue 4 (20th August 2021) - Hina Batool, Syeda; Ali, Amna Farzand; Safdar, Muhammad
Abstract : Purpose: This study aims to investigate social sciences PhD scholars' research experiences through a qualitative lens. Researchers explored the doctoral students' research conceptions, supervision-related expectations, reasons to join PhD, key learning areas and advantages of PhD in this study. Education sector is rigorously seeking PhD faculty and simultaneously offering a number of research degree programs and scholarships to boom the research culture. The amount of time, energy, finance and dedication involved in it urges researchers to investigate this phenomenon holistically. Design/methodology/approach: Qualitative research approach, phenomenology (semi-structured interviews) is used to conduct this research, and interpretative phenomenological analysis technique is used to analyze the collected data. Findings: Findings have been reported comprehensively through interpretative phenomenological analysis. Respondents had a number of expectations from supervisors and viewed this journey as challenging and at the same time beneficial for their professional and personal life. Originality/value: This study is unique in nature, as it depicts research conceptions of doctoral students, benefits of PhD, challenges in pursuing PhD and supervision expectations from a developing country perspective. This study's outcomes have impressions for policymakers, researchers and supervisors. The findings have insights for educators to produce more constructive researchers and scholars.